Pemanfaatan Materi Puisi untuk Meningkatkan Keterampilan Berbicara Siswa - Siti Robiatun Nisa'; Darni Darni; Resdianto Permata Raharjo (Paedagogos: Journal of Education and Learning, 2025)
Speaking skills are an essential component of language competence that should be developed in students from an early stage. This study aims to improve students’ speaking skills through the use of poetry materials as a learning medium. The research employed a mixed-methods approach with an experimental design. The research subjects were seventh-grade students of SMP Darul Ulum Surabaya, selected using purposive sampling, with a total of 30 students. The students were divided into several small groups to facilitate discussion and poetry presentation activities. Data collection techniques included speaking skill tests, observations, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results indicate that the use of poetry materials as a learning medium effectively improves students’ speaking skills, particularly in terms of pronunciation, intonation, fluency, and confidence in expressing ideas. Therefore, poetry-based learning can be considered an effective alternative instructional strategy to enhance students’ speaking skills at the junior high school level.